Hemodynamic subtype classification of type II endoleaks using time-enhanced curves and its association with aneurysmal enlargement - Kota Mitsui, RT, BSc; Yunosuke Nishihara, MD, PhD; Norisato Tsuda, RT, MSc; Manabu Sato, MD, PhD (JVS - Vascular Science)
Objective: This study aimed to: (1) investigate the hemodynamic characteristics of type II endoleaks using mathematical simulations based on pharmacokinetic analysis; and (2) validate the simulation results using clinical data from four-dimensional computed tomography (4D-CT) to assess the relationship between time-enhanced curves (TECs) and aneurysm enlargement. Methods: A mathematical model was created to simulate the hemodynamics of type II endoleaks, incorporating nine compartments representing various cardiovascular components. Simulations were performed under different conditions, leading to the classification of endoleaks into four hemodynamic types. Clinical data were collected from 45 patients who underwent 4D-CT scans at a single center between April 2017 and April 2022. The study cohort included two groups: 20 patients with type II endoleaks identified within 1 week after endovascular aortic repair and 25 patients with persistent type II endoleaks diagnosed during follow-up imaging ranging from 6 months to 9 years post endovascular aortic repair. To evaluate aneurysm volume changes, follow-up CT scans were conducted 6 months or 1 year after the 4D-CT. The primary outcome was evaluating the consistency between simulation results and clinical TEC data obtained from 4D-CT. The secondary outcomes assessed the relationship between individual TEC parameters derived from clinical TEC data and aneurysm enlargement. Results: The mathematical simulations successfully classified type II endoleaks into four hemodynamic types. Clinical validation showed a high concordance between simulation and clinical TEC shapes. A significant difference was observed in various TEC parameters between the stable and enlarged groups. The simulation-based analysis revealed a strong association between aneurysm enlargement and the most informative parameters, including 80% enhancement duration (area under the curve [AUC], 0.88; sensitivity, 0.87; specificity, 0.80; 95% confidence interval [CI], 0.779-0.990; cutoff, 16.9), peak-to-peak timefeeder (AUC, 0.78; sensitivity, 0.93; specificity, 0.60; 95% CI, 0.621-0.937; cutoff, 13.0), and upslope (AUC, 0.86; sensitivity, 0.73; specificity, 0.93; 95% CI, 0.740-0.972; cutoff, 11.7). Conclusions: This study utilized mathematical simulations and clinical validation to characterize the hemodynamics of type II endoleaks. The results demonstrate the strong association of TEC parameters, derived from 4D-CT, with aneurysm enlargement, highlighting their potential for guiding timely intervention in clinical practice. : Clinical Relevance: This study investigates the hemodynamic characteristics of type II endoleaks using four-dimensional computed tomography imaging, demonstrating a significant association between delayed blood flow in the endoleak cavity and aneurysm enlargement at 6 months and 1 year. The findings suggest that hemodynamic subtyping of type II endoleaks could provide valuable insights for predicting aneurysm progression. By identifying patients with delayed blood flow in the endoleak cavity, clinicians may better assess the risk of aneurysm enlargement and tailor follow-up intervals or interventions accordingly. If this method proves effective in more extensive studies, it could significantly improve the management of type II endoleaks by allowing for earlier interventions and more personalized treatment plans, ultimately enhancing patient outcomes.